Proposta metodológica para o ensino dialógico de leitura sob o amparo indisciplinar e decolonial da Linguística Aplicada - Andrade, Francisco Rogiellyson da Silva (2024)
The aim of this thesis is to propose methodological directions for teaching reading based on the philosophical postulates of Dialogical Discourse Theory from the indisciplinary and decolonial perspective of Applied Linguistics. To do this, we list the following specific objectives: a) to demonstrate the relevance of discourse genre analysis in the process of reading interpretation; b) to highlight how the clash of chronotopic relations influences the comprehension of multi-semiotic utterances; c) to analyze, in classroom interactions, the students' evaluative assessments made in their replies; and d) to understand how the activities interfere in the development/refinement of reading skills for responsive-active comprehension of utterances. In order to achieve these objectives, we chose Bakhtin's Dialogical Discourse Theory as our theoretical-philosophical framework, mainly based on the following concepts: chronotope, understood as the spatio-temporal coercions that effect discursive creation and delineate the visions of man and the world enunciated; concrete enunciation, perceived as a link in the interactive chain and as revealing the subject's axiology; discursive genre, seen as the ways in which statements are organized and, consequently, which (re)reveal a unique way of semiotizing the world; and responsive-active comprehension, seen as the basis for triggering the subjects' condition of multiliteracies. We also considered a socio-interactional perspective of the act of reading, in line with proposals that center the development of reading skills in pedagogical practices, the active role of the reader in interpretation and the pillars of decolonial, translingual multiliteracy. Methodologically, we used the assumptions of action research, so the feedback between data generation and intervention in reality is a fundamental clause for research that seeks to problematize practices in which language becomes the central problem, with a view to social and ideological change, in line with the trans- and indisciplinary bias of Applied Linguistics. The corpus of analysis was generated based on interactions in basic education classes in Youth and Adult Education, sixth years of primary school and first years of secondary school. At the end of the study, methodological guidelines are presented for a dialogical pedagogical approach to reading, which, in short, focus on: the demands of the group of students; dialogue between peers; otherness and exotopy; and the process of consumption, production and circulation of utterances. We defend the thesis that a dialogical approach to teaching reading empowers the reader, because it makes them analyze interaction in all its nuances, which make interlocution an event in the ideological clash of discourses. Therefore, we believe that Bakhtinian presuppositions, when dimensioned in reading pedagogy, enhance the production of teaching methodologies capable of providing the reader (always) in training with the perception of their responsive-active position in interaction via reading, altering their discursive capacity to engage in the different multiliteracies practices that organize their enunciative needs.